2019
DOI: 10.1002/cam4.2802
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning pathological microscopic features in endemic nasopharyngeal cancer: Prognostic value and protentional role for individual induction chemotherapy

Abstract: Background To explore the prognostic value and the role for treatment decision of pathological microscopic features in patients with nasopharyngeal carcinoma (NPC) using the method of deep learning. Methods The pathological microscopic features were extracted using the software QuPath (version 0.1.3. Queen's University) in the training cohort (Guangzhou training cohort, n = 843). We used the neural network DeepSurv to analyze the pathological microscopic features (DSPMF) and then classified patients into high‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…Impressively, we found that clinic, histopathologic, and radiomic signatures exhibited complementary value in pretreatment individualized prediction of prognoses, with the best performance in pretreatment individualized prediction of prognoses in two test cohorts (Table 2). Compared with previous radiomic and histopathologic models (C-index 0.723-0.761), 10,19 our results also showed an impressive improvement (C-index > 0.8 in three cohorts). We believed these improvements might come from the maximum mining of clinic data on different spatial scales.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Impressively, we found that clinic, histopathologic, and radiomic signatures exhibited complementary value in pretreatment individualized prediction of prognoses, with the best performance in pretreatment individualized prediction of prognoses in two test cohorts (Table 2). Compared with previous radiomic and histopathologic models (C-index 0.723-0.761), 10,19 our results also showed an impressive improvement (C-index > 0.8 in three cohorts). We believed these improvements might come from the maximum mining of clinic data on different spatial scales.…”
Section: Discussionsupporting
confidence: 57%
“…A recent study about NPC showed a signature based on handcrafted features from WSI as an independent prognostic factor, with a similar performance (C-index 0.723). 19 In contrast, our histopathologic signature was constructed in an end-to-end method, avoiding incompleteness and instabilities of artificial setting. To interpret the histopathologic signature, we visualized DCNN using the attention map, 30 and found the hotspots located on the tumor cells with multiple nucleoli ( Figure 4a ), vesicular nuclei ( Figure 4b ), and spindle shape ( Figure 4c , as sarcomatoid tumor cells).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In developing the prognostic use of QuPath as a tool for annotation training for deep learning, Liu et al [40] showed in 843 samples that their network could stratify patients with nasopharyngeal carcinoma into a high risk group with shorter than 5 year progression free survival (p < 0.0001).…”
Section: Methodsmentioning
confidence: 99%